The Influence of Base Layer Thickness in Flexible Pavements - Hadi, M. A. S.; Al-Sherrawi, M. H. (Engineering, Technology & Applied Science Research, 2021)
Flexible pavement design and analysis were carried out in the past with semi-experimental methods, using elastic characteristics of pavement layers. Due to the complex interferences between various layers and their time consumption, the traditional pavement analysis, and design methods were replaced with fast and powerful methods including the Finite Element Method (FEM) and the Discrete Element Method (DEM). FEM requires less computational power and is more appropriate for continuous environments. In this study, flexible pavement consisting of 5 layers (surface, binder, base, subbase, and subgrade) had been analyzed using FEM. The ABAQUS (6.14-2) software had been utilized to investigate the influence of the base layer depth on vertical stresses and displacements. Three different thicknesses were adopted (10, 20, and 30cm) with constant other pavement layer thicknesses. The results of this study showed that the stress levels at the top of the base layer increased by about 37% when the thickness of this layer increased from 10cm to 30cm, while the stress levels at the top of the subbase layer decreased by about 64%. When the base layer increased from 10 to 20, from 20 to 30, and from 10 to 30cm the vertical displacement decreased by 18%, 24%, and 37% respectively.